IMPLEMENTATION OF E-GOVERNMENT IN REALIZING EXCELLENT SERVICE IN METRO CITY POPULATION AND CIVIL REGISTRATION OFFICES DURING THE COVID-19 PANDEMIC - Amantha, Goestyari Kurnia; Rahmaini, Putri; Sari, Tia Marlinda (Universitas Muhammadiyah Lampung, 2024)
Public satisfaction with the quality of public services in Indonesia is still very low, this is evident from the many complaints and public dissatisfaction with the public service process provided by the government. The COVID-19 pandemic has had a significant impact on various community activities, including public sector service activities. The high number of Covid-19 cases in Lampung Province had even resulted in almost all regencies and cities simultaneously being included in the red zone category, however the COVID-19 pandemic did not reduce the urgency of the need for high population administration and civil registration services, so that the implementation of e-government is a way of life. provide excellent service during the covid-19 pandemic. The purpose of this study is to see how the implementation of e-government in realizing excellent service during the covid-19 pandemic. The methodology used is descriptive qualitative where data and information are obtained through interviews, observations and documentation, so as to provide a direct description of the research results. Based on the research results, the implementation of e-government at the Department of Population and Civil Registration of Metro City has reached the second stage, namely interaction. This is based on the ability to represent the stages of web presence and interaction by aligning the concept of excellent service with the fulfillment of aspects of attitude, attention, action, ability, appearance, and responsibility. Meanwhile, at the transaction and transformation stage as a benchmark for the implementation of e-government, it has not been implemented comprehensively if it is associated with aspects of excellent service.